Simplified methodologies for assessing the out-of-plane two-way bending seismic response of unreinforced brick masonry walls: lessons from recent experimental studies. (October 2021) - Sharma, S.; Tomassetti, U.; Graziotti, F.; Magenes, G.
Abstract: This paper describes a simplified methodology for the assessment of unreinforced masonry (URM) walls under out-of-plane two-way bending seismic action. The methodology involves a force-based check derived from the principle of virtual work. This check is proposed based on experimental observations of significant cracking resistance associated with two-way spanning URM walls, indicating methodologies considering such walls to be pre-cracked or to be non-laterally supported as overly conservative. The methodology incorporates several findings and developments from recent experimental campaigns: ranging from novel characterization tests on masonry couplets to incremental dynamic tests on full-scale buildings. Such incorporations include new formulation to calculate the torsional shear strength of a bed joint and accounting for possible changes in the boundary conditions of an OOP wall during dynamic loading. Testing standards as well as recommendations in several international guidelines for masonry structures addressing the input properties required to implement the proposed methodology are enlisted and reviewed. The methodology requires the definition of the period of vibration of the assessed URM walls, to calculate which plate theory based formulation is provided. Open research questions and potential avenues for further development of the methodology are ultimately highlighted.